The determination of field usability of method measuring temperature fields in the air using an infrared camera - Pešek, Martin; Pech, Ondřej (EDP Sciences, 2014)
The article deals with the field usability determination of the method for measuring temperature fields in the air using an infrared camera. This method is based on the visualization of temperature fields on an auxiliary material, which is inserted into the non-isothermal air flow. In this article the field usability is determined from time constants of this method, which define borders of usability for low temperature differences (between air flow temperature and surrounding temperature) and for low air flow velocities. The field usability determination for measuring temperature fields in the air can be used in many various applications such as air-heating and air-conditioning where the method of measuring temperature fields in the air by infrared camera can be used.

The article deals with the field usability determination of the method for measuring temperature fields in the air using an infrared camera. This method is based on the visualization of temperature fields on an auxiliary material, which is inserted into the non-isothermal air flow. In this article the field usability is determined from time constants of this method, which define borders of usability for low temperature differences (between air flow temperature and surrounding temperature) and for low air flow velocities. The field usability determination for measuring temperature fields in the air can be used in many various applications such as air-heating and air-conditioning where the method of measuring temperature fields in the air by infrared camera can be used.
The determination of field usability of method measuring temperature fields in the air using an infrared camera
Keywords: Infrared camera; temperature fields; air stream; Infrared camera; temperature fields; air stream